Musyarakah Mutanaqisah home financing product : an implementation analysis in Affin Islamic Bank Berhad / Muhammad Syafiq Muhammad Hatta. - Muhammad Hatta, Muhammad Syafiq (2020)
This research serve the purpose to analyze the implementation of home financing product using musyarakah mutanaqisah contract. This research is made to focus on the implementation at Affin Islamic Bank Berhad. Musyarakah mutanaqisah is a diminishing contract. This means that the ownership of one party will decrease while the other will increase. This contract is used in home financing product at Islamic bank institutions. This contract is way better than the other contract, Bay’ Bithaman Ajil (BBA). This research problem is the customers are not clear on the act of the musyarakah mutanaqisah contract in home financing at Islamic banking institutions. This research objectives are first, to identify the musyarakah mutanaqisah according to Islamic perspective. Second, to analyse the implementation of musyarakah mutanaqisah home financing product at Affin Islamic Bank Berhad. As for collecting data, the researcher has use qualitative method which is document analysis and semi-structure interview. The finding shows that musyarakah mutanaqisah contract is being applied in the home financing product following the guidelines of Shariah. The contract is implemented in accordance to Shariah guidelines because it must be Shariah compliance contract. This way the contract could be accepted to be implemented in Islamic banking institutions. There are no elements of interest, uncertainty and gambling in this contract because it will be the same as conventional loan. This contract is needed in the Islamic banking so that the Muslim could buy houses using Islamic contract and for the non-Muslim, it could be another option for them. This contract is beneficial for both Muslim and non-Muslim customers. The implication of this contract is that it will make both parties beneficial. Both parties will get their benefit when they are binding in this contract.